2016
DOI: 10.1021/acs.joc.6b00793
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective and Stereospecific Dehydrogenative Annulation Utilizing Silylium Ion-Activated Alkenes

Abstract: Treatment of dialkylbenzylsilanes (1) with trityl tetrakis(pentafluorophenyl)borate (TPFPB) afforded the corresponding silylium ions in equilibrium with their intra- or intermolecular π-complexes, which underwent dehydrogenative annulation with various alkenes to form 1,2,3,4-tetrahydro-2-silanaphthalenes (4) in up to 82% isolated yield. Sterically bulkier substituents on the silicon atom tended to increase the yield of cyclic products 4. The annulation products retained the stereochemistry in cases of the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Silylium ions are extremely reactive species that are generally difficult to isolate and characterize, unless they are stabilized by coordination with a solvent or through an external or internal Lewis base (LB) . This exacerbated reactivity has long delayed their isolation compared to carbocations, isolated and characterized nearly 100 years earlier .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silylium ions are extremely reactive species that are generally difficult to isolate and characterize, unless they are stabilized by coordination with a solvent or through an external or internal Lewis base (LB) . This exacerbated reactivity has long delayed their isolation compared to carbocations, isolated and characterized nearly 100 years earlier .…”
Section: Introductionmentioning
confidence: 99%
“…However, these silicon species are only of synthetic interest if they are previously pacified and their reactivity controlled. The work of Siegel, Müller, Oestreich, and others has shown that the interaction between the cationic silylated center and Lewis basic substituents is able to control this reactivity and to modulate the Lewis acidity of silicon . Very recent studies have demonstrated that the addition of basic and chiral ligands around the silyl cation not only stabilizes the latter but also allows chirality transfer with satisfactory enantioselectivity levels in Diels–Alder reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Given our interest in the development of direct C–H functionalization and photoinduced annulation as well as the existence of limited literature reports on dehydrogenative annulation, which was thought to require transition metals and/or oxidative additives, , in this letter, we report an efficient transition-metal-free photoinduced intramolecular dehydrogenative annulation of 4 H -chromen-4-ones for the synthesis of benzo­[ c ]­furo­[2,3- a ]­xanthenone derivatives that does not require catalysts or additives (Scheme b).…”
mentioning
confidence: 99%
“…We have extended silyl cation chemistry to the synthesis of silacyclic compounds and reported the synthesis of 1,2-dihydro-2-silanaphthalenes using alkynes [25,26]. The intramolecular addition of a silyl cation toward a C-C triple bond rather than an intermolecular one is expected to lead to a benzosilole by an appropriate reaction of the resulting ethenyl carbocation.…”
Section: Resultsmentioning
confidence: 99%